INTEGRATION OF SUFISM IN THE BUKHARA EMIRATE AND ITS COMPATIBILITY WITH SOCIAL AND CULTURAL LIFE (Scientific journal of the Fergana State University, 2024)
Inthisarticle, the development of scienceandIslamicsciencesin the Bukhara Emirate, itanalyzes the activities of the Bukharaemirs, the peculiarities of the socio-spiritualenvironmentandepoch.Inparticular,in the emirate, the incentivetostudy the Koran,Hadith,Fiqhandmysticism is revealedon the basis of primary sources, the role of whichin the spirituallife of people.